Investigation of the bone density in multiple sclerosis - O. S. Dranichnikova; V. D. Zavadovskaya; V. M. Alifirova (Бюллетень сибирской медицины, 2008)
A number of investigations revealed a problem of osteopenic syndrome in patients with multiple sclerosis but there is no common opinion concerning factors which lead to its development. We observed 65 patients with multiple sclerosis with various type of its course and disability status of several degree based upon EDSS scale. Ultrasound osteometry of the calcaneus, computer tomography of QCT of L1—L3 vertebras were performed, serum crosslaps, N-MID osteocalcin were used. Decreased bone density, injured bone microarchitectonics and suppression of bone formation and resorption, which were correlated EDSS were found. Correlations with other factors (growth, weight, gender, and number of steroid therapy sessions ) for these parameters was not revealed. This allowed to conclude that the main reason of decreased bone mass in patients with multiple sclerosis is the dramatic decrease in physical activity.